Permanent Inactivation of HBV Genomes by CRISPR/Cas9-Mediated Non-cleavage Base Editing - Yang, Yu-Chan (Mol Ther Nucleic Acids, 2020)
Current antiviral therapy fails to cure chronic hepatitis B virus (HBV) infection because of persistent covalently closed circular DNA (cccDNA). CRISPR/Cas9-mediated specific cleavage of cccDNA is a potentially curative strategy for chronic hepatitis B (CHB). However, the CRISPR/Cas system inevitably targets integrated HBV DNA and induces double-strand breaks (DSBs) of host genome, bearing the risk of genomic rearrangement and damage. Herein, we examined the utility of recently developed CRISPR/Cas-mediated “base editors” (BEs) in inactivating HBV gene expression without cleavage of DNA. Candidate target sites of the SpCas9-derived BE and its variants in HBV genomes were screened for generating nonsense mutations of viral genes with individual guide RNAs (gRNAs). SpCas9-BE with certain gRNAs effectively base-edited polymerase and surface genes and reduced HBV gene expression in cells harboring integrated HBV genomes, but induced very few insertions or deletions (indels). Interestingly, some point mutations introduced by base editing resulted in simultaneous suppression of both polymerase and surface genes. Finally, the episomal cccDNA was successfully edited by SpCas9-BE for suppression of viral gene expression in an in vitro HBV infection system. In conclusion, Cas9-mediated base editing is a potential strategy to cure CHB by permanent inactivation of integrated HBV DNA and cccDNA without DSBs of the host genome.